Thickness measurement of non-magnetic steel plates using a novel planar triple-coil sensor. (October 2019) - Lu, Mingyang; Meng, Xiaobai; Yin, Wuliang; Qu, Zhigang; Wu, Fanfu; Tang, Jiawei; Xu, Hanyang; Huang, Ruochen; Chen, Ziqi; Zhao, Qian; Zhang, Zhijie; Peyton, Anthony
Abstract: In the eddy current testing, the impedance tested by the sensor is influenced by the lift-off between the sensor and the sample plate. Consequently, the thickness inferred from the measured impedance is also affected by the lift-off. In this paper, a novel planar triple-coil air-core sensor is designed, in which three coils (two excitation coils and one receiving coil) with different radii are co-axially arranged in the same plane. Based on this sensor setup, an algorithm for the thickness measurement of the non-magnetic metallic plate is proposed. By using the transmitter-receiver combinations and the proposed algorithm, the measured thickness is almost immune to the lift-off variation. Moreover, previously the measurement of thickness requires a complex frequency feature – peak frequency for the real part of the impedance, which is obtained from the multi-frequency impedance or inductance spectra (frequency-sweeping mode), while with the method proposed in this paper, only single frequency measurement is needed, hence relaxing the instrument and measurement requirements. This method has a potential of on-line real-time measurement of the thickness for non-magnetic steel plates.